(untitled) (Universal International Scientific Journal, 2026)
this article presents a theoretical and empirical analysis of the interrelationship between students’ socio-psychological adaptation and their psychological safety within the educational environment. Socio-psychological adaptation is defined as the student’s ability to integrate into the school environment, adjust to teacher expectations, and maintain social relationships with peers. Psychological safety is conceptualized as the student’s internal feeling of emotional stability, social acceptance, and security in school. The article substantiates that both constructs are mutually reinforcing and must be addressed together to ensure holistic student development. Pedagogical and psychological strategies such as psychological climate monitoring, differentiated instruction, social support mechanisms, and school psychological services are suggested as effective solutions